Ethnic advertising: adolescents’ attitudes towards target and non-target advertisements - Butt, Mohsin; de Run, E. (Emerald Group Publishing Limited, 2010)
Purpose – This article aims to explore attitudinal and behavioural differences between target and non-target groups of ethnic advertisements. It seeks to expand the existing body of knowledge by investigating these differences from the perspective of young consumers in an Eastern context. This helps in testing the established theories of distinctiveness and cultural schemas in an Eastern society. Design/methodology/approach – The study sample consists of 1,600 randomly selected adolescents from different states of Malaysia. Data were analysed using MANOVA, ANOVA and t-test to explore the group differences between adolescents based on their ethnicity and advertisement type. Findings – The results indicate a significant group difference between target and non-target respondents to the advertisement. It also shows that ethnicity is a viable target variable for both majority and minority ethnic groups in Malaysia. Research limitations/implications – Although there are many ethnic groups in Malaysia this research only investigated two ethnic groups. Therefore, the results may not be applicable to other ethnic minority groups in Malaysia. Originality/value – The study explores the possibility of using ethnicity as a target variable for adolescents in an Eastern context. It investigates the issue in a holistic manner by incorporating views from target as well as non-target groups.